Elotuzumab in combination with thalidomide and low‐dose dexamethasone: a phase 2 single‐arm safety study in patients with relapsed/refractory multiple myeloma. (19th July 2016) - Mateos, María‐Victoria; Granell, Miguel; Oriol, Albert; Martinez‐Lopez, Joaquin; Blade, Joan; Hernandez, Miguel T.; Martín, Jesus; Gironella, Mercedes; Lynch, Mark; Bleickardt, Eric; Paliwal, Prashni; Singhal, Anil; et al.
Summary: Elotuzumab is an immunostimulatory, humanized immunoglobulin G1 monoclonal antibody that selectively targets and kills signalling lymphocytic activation molecule family member 7–expressing myeloma cells. We evaluated the safety and tolerability of elotuzumab 10 mg/kg combined with thalidomide 50–200 mg and dexamethasone 40 mg (with/without cyclophosphamide 50 mg) in patients with relapsed/refractory multiple myeloma (RRMM). The primary endpoint was the proportion of grade ≥3 non‐haematological adverse events (AEs); other endpoints included the number of dose reductions/discontinuations and efficacy. Forty patients were treated, who had a median of three previous therapies, including bortezomib (98%) and lenalidomide (73%). Grade ≥3 non‐haematological AEs were reported in 63% of patients, most commonly asthenia (35%) and peripheral oedema (25%). Six (15%) patients had an infusion reaction. Twenty‐six (65%) patients had ≥1 dose reduction/discontinuation due to an AE, none related to elotuzumab. Overall response rate was 38%; median progression‐free survival was 3·9 months. Median overall survival was 16·3 months and the 1‐year survival rate was 63%. Minimal incremental toxicity was observed with addition of elotuzumab to thalidomide/dexamethasone with or without cyclophosphamide, and efficacy data suggest clinical benefit in a highly pre‐treated population. Elotuzumab combined with thalidomide may provide an additional treatment option for patients with RRMM.